GAME: A SURVEY ON AWARENESS AND UTILISATION OF PRIMARY TEACHERS IN SOUTH WEST NIGERIA - Odewumi, Michael Olubunmi; Bada, Tayo Abass (Indonesian Journal of Early Childhood Education Studies, 2019)
Game has become an imperative source of improvement and innovation of efficiency for instructors across the globe, yet the awareness and utilisation are still lacking by the primary school teachers especially on creative arts instruction.  Therefore, this paper investigated the perception of primary school teachers on awareness and utilisation of game for teaching and learning of creative arts in South-west, Nigeria. Teachers in the both public and private primary school in the South-west, Nigeria were sampled purposively.  The study was a descriptive type by means of survey method. 2 research questions were forwarded and answered with 4 hypothesises tested at 0.05 significant levels.  The research designed instrument was validated by experts and reliability coefficient of 0.72, and 0.79 were realised.  Data collected through structured questionnaire were answered by mean and percentage. The four hypothesises were analysed with t-test.  The findings show that primary school teachers had positive perception on the awareness and utilisation of game for learning of Creative Arts. It was concluded that primary school teachers perceived game to be important and easy to utilise in facilitating teaching learning. The study further recommended that the teachers in primary education classes should be encouraged to utilise game for teaching and learning.